2022
DOI: 10.1109/tiv.2022.3200592
|View full text |Cite
|
Sign up to set email alerts
|

Driving Performance Under Violations of Traffic Rules: Novice vs. Experienced Drivers

Abstract: It is of great significance for safe driving to study drivers' eye movement and driving operation behavior when they encounter other road users violating traffic rules. The underlying reason is that most drivers are unable to process the unexpected visual stimulation, which is more likely to lead to driving accidents, especially in a hybrid situation. In this study, a driving simulator is used to design driving scenarios and study the driving performance of drivers with different driving experiences when other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 16 publications
(16 reference statements)
0
18
0
1
Order By: Relevance
“…Central fixation bias, which is a key factor in driving tasks as evidenced in Xu et al., 4 particularly for experienced drivers, is not thoroughly reflected in previous research. It is reported that human vision exerts a tendency of central fixation bias to actively search the gist of approaching scenes and bind visual features for higher cognitive understanding; that is, the visual information from the central visual field/region is paid more attention while that from outer regions is paid less attention.…”
Section: Human Factors In Drivingmentioning
confidence: 81%
“…Central fixation bias, which is a key factor in driving tasks as evidenced in Xu et al., 4 particularly for experienced drivers, is not thoroughly reflected in previous research. It is reported that human vision exerts a tendency of central fixation bias to actively search the gist of approaching scenes and bind visual features for higher cognitive understanding; that is, the visual information from the central visual field/region is paid more attention while that from outer regions is paid less attention.…”
Section: Human Factors In Drivingmentioning
confidence: 81%
“…A negative skew indicates that the left tail is longer, while a positive skew indicates a longer right tail. The mathematical equation for skewness ( Yu et al, 2021 ; Zhang et al, 2021 ; Qi et al, 2022 ; Zheng et al, 2023c ) is where are the individual sample points, is the sample mean, s is the standard deviation ( Liu et al, 2021 ; J, X. et al, 2022; Mao et al, 2022b ; Guo et al, 2022 ; Xu et al, 2022b ), and N is the number of samples. Figure 7 shows skewness for different activities over both datasets.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction of LPCCs from accelerometer signals [67], the primary step involves the application of linear predictive analysis (LPA). Given 𝑠(𝑛) as the accelerometer signal, it can be modeled by the relation…”
Section: Linear Prediction Cepstral Coefficients (Lpccs)mentioning
confidence: 99%